Ambiguity Resolution for Sketched Diagrams by Syntax Analysis Based on Graph Grammars - Brieler, Florian; Minas, Mark (Electronic Communications of the EASST, 2008)
Sketching, i.e., drawing diagrams by hand and directly on the screen, is gaining popularity, as it is a comfortable and natural way to create and edit diagrams. Hand drawing is inherently imprecise, and often sloppy. As a consequence, when processing hand drawn diagrams with a computer, ambiguities arise: it is not always clear what part of the drawing is meant to represent what component. Resolution of these ambiguities is the main issue of sketching. Ambiguity can only be solved by exploring the context of ambiguous components. This paper describes ambiguity resolution by syntax analysis in DiaGen, a generic framework for generating diagram editors. Such editors support free-hand editing (which is closely related to sketching), and allow for analyzing the created diagrams based on a hypergraph grammar. Our approach adds support for sketching to the generated editors. In order to resolve the ambiguities in sketched diagrams, DiaGen’s diagram analysis based on graph parsing is used. The necessary modifications to DiaGen and its graph parser in particular are discussed.